Mentoring in organizations: Implications for women - Burke, R. J. (Journal of business ethics, 1990)
This paper reviews the literature on the mentoring process in organizations and why mentoring can be critical to the career success of women managers and professionals. It examines some of the reasons why it is more difficult for women to find mentors than it is for men. Particular attention is paid to potential problems in cross-gender mentoring. A feminist perspective is then applied to the general notion of mentorships for women. The paper concludes with an examination of what organizations can do to further mentor relationships and an agenda for further research in this area.